(untitled) (International Journal of Engineering and Computer Science, 2017)
A Self-Healing Network is one, which is used to focus on how to reduce the complexity and cost of the management of dependability policies and mechanisms without human intervention. It also has to monitor the Network Traffic to predict the abnormal traffic patterns. The main objectives of this Self-Healing Network is to spot the problems before they occur, to know immediately when problems arise, to share available data with stakeholders, to detect the security breaches i.e., this network aims at ensuring that the service will continue to work regardless of defects that might occur in the network. One of the problems is chosen to solve as an initial work. When users are accessing any service from the server, the server may unexpectedly close the connection, thus sending an empty response. The tool designed tries to rectify this problem without the knowledge of the user and thus avoids manual fixing of this fault. Nowadays , Internetwork outer surfaces the some of the challenges and tasks based upon the utilization and incremental growth of the users. Prerequisites involved in the network are multipath, multi-home, mobility etc. Here we discussed the techniques which increases the employability of user data transmission through the multipath. Although the several techniques involved, in this paper we target the tunnelling strategy based upon the scalability, performance and time consumption is regarded.